2009
DOI: 10.1038/nm.1963
|View full text |Cite
|
Sign up to set email alerts
|

Impaired gastric acidification negatively affects calcium homeostasis and bone mass

Abstract: Activation of osteoclasts and their acidification-dependent resorption of bone is thought to maintain proper serum calcium levels. Here we show that osteoclast dysfunction alone does not generally affect calcium homeostasis. Indeed, mice deficient in Src, encoding a tyrosine kinase critical for osteoclast activity, show signs of osteopetrosis, but without hypocalcemia or defects in bone mineralization. Mice deficient in Cckbr, encoding a gastrin receptor that affects acid secretion by parietal cells, have the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
136
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 179 publications
(148 citation statements)
references
References 45 publications
6
136
0
6
Order By: Relevance
“…This CaR-dependent gastrin response to Ca 2+ forms the basis for the diagnostic Ca 2+ stimulation test in patients with Zollinger-Ellison (ZES) syndrome, whose gastrinomas express CaR, and this also explains the observed exacerbation of acid hypersecretion in multiple endocrine neoplasia type 1 patients with hyperparathyroidism and ZES (15). Because acid promotes Ca 2+ absorption, the CaR-expressing G cell behaves like a Ca 2+ regulatory cell, as evidenced by the fact that gastrin receptor null mice become hypocalcemic (22).…”
Section: Low Basal Gastrin and Absent Gastrin Response To Luminal Nutmentioning
confidence: 99%
“…This CaR-dependent gastrin response to Ca 2+ forms the basis for the diagnostic Ca 2+ stimulation test in patients with Zollinger-Ellison (ZES) syndrome, whose gastrinomas express CaR, and this also explains the observed exacerbation of acid hypersecretion in multiple endocrine neoplasia type 1 patients with hyperparathyroidism and ZES (15). Because acid promotes Ca 2+ absorption, the CaR-expressing G cell behaves like a Ca 2+ regulatory cell, as evidenced by the fact that gastrin receptor null mice become hypocalcemic (22).…”
Section: Low Basal Gastrin and Absent Gastrin Response To Luminal Nutmentioning
confidence: 99%
“…Moreover, IL-11 is key in gastric damage, mucosal repair and gastric cancer progression (27,28). Since the detected osteoclastogenesis did not correlate with the presence of bone metastases, we suggested an alternative hypothesis to explain it, considering a potential relationship between an increased osteoclastogenesis and the gastric acid levels, which are known to affect OC activity (29). We observed that some patients with increased osteoclastogenesis also showed chronic gastritis and referred to taking proton-pump inhibitors (data not shown).…”
Section: Discussionmentioning
confidence: 89%
“…In addition, the widespread use of PPI among elderly patients has recently been linked to increased fracture risk and disrupted calcium absorption [37,38]. Yang and coworkers found an association between long-term PPI therapy and an increased risk of hip fracture, which led us to investigate this issue within our study cohort.…”
Section: Discussionmentioning
confidence: 93%